2004
DOI: 10.1111/j.1532-849x.2004.04002.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mechanical and Thermal Properties of Commonly Used Denture Base Resins

Abstract: The microwaveable resins displayed better adaptation, greater stiffness, and greater surface hardness than other denture base resins included in this investigation. Elastomeric toughening agents yielded decreased stiffness, decreased surface hardness, and decreased glass transition temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 24 publications
5
95
0
5
Order By: Relevance
“…Since the introduction of POMs, there has been a continued interest in its use for PRDP applications [1, 10,20,37,48,61]. Chu considered it a simple and effective means of improving PRDP aesthetics [10].…”
Section: Thermoplastic Resins and Prdpsmentioning
confidence: 99%
“…Since the introduction of POMs, there has been a continued interest in its use for PRDP applications [1, 10,20,37,48,61]. Chu considered it a simple and effective means of improving PRDP aesthetics [10].…”
Section: Thermoplastic Resins and Prdpsmentioning
confidence: 99%
“…It is known that the unreacted monomer may act as a plasticizer, thereby increasing the resilience 15 and decreasing the strength of the polymerized resin 16 . It may be concluded that color and the presence of nylon fibers in acrylic resins did not affect the properties analyzed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…A chest x-ray was taken for the nine specimens in different concentration of BaSO 4 and compared with an aluminum stepwedge; the aluminum was composed of nine steps and each step of the aluminum equal to 1mm and the specimens to be equal to 2 mm of the aluminum as a standard for radiographic evaluation. A light transmission densitometer was to measure the difference in the image density of all specimens which contain a different concentration of BaSO 4 nanoparticles in comparison with non-modified Acetal resin and aluminum step wedge.…”
Section: Evaluation the Radio-opacity Of Specimensmentioning
confidence: 99%
“…3 It is very strong, resists wear and fatigue, in addition to flexiblity, which makes it the best material for pre-formed clasps of partial denture, unilateral partial denture, provisional bridges, implant abutments, occlusal splints and orthodontic appliances. 4 Acetal resin and polymethyl methacrylate (PMMA) are radiolucent materials that cannot be seen using standard radiographic techniques. So in cases of accidental ingestion, aspiration traumatic impactions of the dental appliance, it is difficult to be detected and requires invasive procedures as advanced imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation